Macroalgae-based bio-based packaging: Characteristics, green extraction methods, and applications as sustainable solutions - Sarifah Supri; Wen Xia Ling Felicia; Mariah Aqilah Mohd Affandy; Birdie Scott Padam; Asep Awaludin Prihanto; Kobun Rovina (Indonesian Society for Knowledge and Human Development, 2025)
Macroalgae represents a sustainable and environmentally friendly resource for developing bio-based packaging materials to prolong the shelf life of fruits and vegetables. This review explores the unique properties of red, brown, and green algae, rich in bioactive compounds that offer significant advantages as bio-based packaging materials. The review highlights green extraction methods such as supercritical fluid extraction, enzymatic-assisted extraction, microwave-assisted extraction, and ultrasound-assisted extraction, which optimize the yield of the bioactive compounds. These methods are advantageous over conventional techniques due to their low solvent usage, high selectivity, rapid processing, and reduced extract degradation. Additionally, the review delves into macroalgae's antioxidant and antimicrobial properties and their impact on enhancing the shelf life of perishable produce. Regulatory aspects concerning incorporating macroalgae compounds into food packaging materials are examined alongside consumer perceptions and acceptance of these innovative packaging solutions. The widespread consumption of macroalgae in ASEAN countries underscores its safety and familiarity, paving the way for broader acceptance of macroalgae-based packaging in global markets. In summary, utilizing macroalgae in bio-based packaging presents a sustainable solution to food preservation. It leverages the bioactive properties of algae to extend the shelf life of fruits and vegetables. This review underscores the potential of macroalgae as a viable alternative to conventional packaging materials, aligning with global sustainability goals and consumer preferences for eco-friendly products.